2013
DOI: 10.1007/s00338-013-1098-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on the skeletal chemistry of cultured scleractinian zooxanthellate corals: Cd/Ca ratio as a potential proxy for salinity reconstruction

Abstract: The effect of salinity on the elemental and isotopic skeletal composition of modern zooxanthellate scleractinian corals (Acropora sp., Montipora verrucosa and Stylophora pistillata) was investigated in order to evaluate potential salinity proxies. Corals were cultured in the laboratory at three salinities (36, 38 and 40). The other environmental parameters were kept constant. For all species analyzed, Sr/Ca, Mg/Ca, U/Ca and Li/Ca ratios were not influenced by salinity changes. The Ba/Ca ratio also lacks a syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 94 publications
4
9
0
Order By: Relevance
“…Results presented in this study are in agreement with previous laboratory investigations from Zhong and Mucci (1989) which concluded that for synthetic aragonite precipitated in seawater solutions of various salinities (from 5 to 44 psu), the incorporation of Sr 2+ is unaffected by salinity variations. Our results are also in agreement with the recently published work of Pretet et al (2013), who investigated the effect of salinity on the skeletal chemistry of cultured corals Acropora sp., Montipora verrucosa and Stylophora pistillata. The three coral genera were bred in three different aquaria with artificial seawater and at a salinity of 36, 38 and 40 psu, respectively.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Results presented in this study are in agreement with previous laboratory investigations from Zhong and Mucci (1989) which concluded that for synthetic aragonite precipitated in seawater solutions of various salinities (from 5 to 44 psu), the incorporation of Sr 2+ is unaffected by salinity variations. Our results are also in agreement with the recently published work of Pretet et al (2013), who investigated the effect of salinity on the skeletal chemistry of cultured corals Acropora sp., Montipora verrucosa and Stylophora pistillata. The three coral genera were bred in three different aquaria with artificial seawater and at a salinity of 36, 38 and 40 psu, respectively.…”
Section: Resultssupporting
confidence: 93%
“…Nevertheless, these studies were rather local and did not encompass a large salinity range. A recent laboratory experiment based on three different coral genera (Acropora sp., Montipora verrucosa and Stylophora pistillata) found no effect of salinity (in the range 36-40 psu) on Sr / Ca, but this study did not encompass the Porites genus (Pretet et al, 2013).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Following the release of the Fourth and Fifth Assessment Reports of the Intergovernmental Panel on Climate Change the scarcity of paleoclimate data representing tropical marine environments and the southern hemisphere has become increasingly clear [e.g., Intergovernmental Panel on Climate Change , ; Masson‐Delmotte et al , ]. Of the available high‐resolution paleoclimate records, coral colonies are particularly useful because skeletal geochemistry can provide subannual time series data on past water temperature [ Bagnato et al , ; DeLong et al , ; Epstein et al , ; Gagan et al , ; Grottoli and Eakin , ; McCrea , ], salinity [ Corrège , ; Felis et al , ; Gagan et al , ; Hendy et al , ; Le Bec et al , ; Pretet et al , ; Wu et al , ], pH [ Hemming and Hanson , ; Pelejero et al , ; Shinjo et al , ; Wei et al , ], and nutrient concentration [ LaVigne et al , , ]. On a global scale, such proxy data can help unravel Earth's natural climate variability and therefore improve computer model predictions of future climate.…”
Section: Introductionmentioning
confidence: 99%
“…Slightest unintended variations in water parameters can cause significant effects to reef organisms [71][72][73][74]. Therefore, high-quality seawater is an important prerequisite for ensuring meaningful and comparable results in experimental systems [20,26].…”
Section: Quality Control and Maintenance Of Seawatermentioning
confidence: 99%